„OBCA” I „SWOJA”. DWIE IRENY, DWIE ŻONY JEDNEGO WŁADCY BAZYLEGO WIELKIEGO KOMNENA - Cyrulski, Marcin (Collectanea Philologica, 2013)
Basil Grand-Comnenos, Emperor of Trebizond, was famous for his bigamy. In 1339 he married Irene of Trebizond, although he had a wife – also Irene – a natural daughter of Andronikos III Palaiologos. After the sudden death of Basil, his first wife took over the thron of Trebizonde. Her reign soon came to the end. She was “foreign” to the Trapezuntine aristocracy. Definitively Irene of Trebizond, the second wife of Basil, triumphed when her son Alexius III had ascended the throne of Empire of Trebizond.